Pigs, people, and proximity: a 6000-year isotopic record of pig management in Ireland - Eric Guiry; Fiona Beglane; Finbar McCormick; Eric Tourigny; Michael P. Richards (Royal Society Open Science)
The ways that pigs interact with humans are more flexible than other livestock. This plasticity means that pig behaviour can evidence a tremendous range of cultural phenomena, some of which may not otherwise show up in the archaeological record. We explore how people and pigs interacted in Ireland over 6000 years (4000 BC–AD 1900) from the perspective of isotopic zooarchaeology, using a large sample of pigs from 40 sites. Results demonstrate continuity and dramatic change. While pig diets show an emphasis on pannage throughout much of the period, husbandry was fundamentally reconstructed in the early medieval period. Through prehistory, pigs were herded in areas distant from human settlements, whereas later they were relocated to live near people. We explore potential implications of these patterns at a range of scales, from economics, to perspectives on zoonoses, and animal agency. While syntheses of a similar scope are needed for other areas of Europe, these findings may reflect a uniquely Irish trajectory of human–animal relationships.